Pengaruh Organo-mineral Terhadap Beberapa Sifat Kimia Tanah dan Hasil Jagung pada Ultisol Jatinangor - Rija Sudirja; Yuliati Machfud; Emma Trinurani Sofyan; Benny Joy; Santi Rosniawaty; Rani Ros (Fakultas Pertanian Universitas Padjadjaran, 2018)
The use of organic materials and minerals as fertilizer needs to be developed in order to increase agricultural productivity, especially in soils marginal that are widely distributed on the Indonesian. This study aims to determine the productivity of soil and corn plants by using various formulations of organo-mineral materials in the Ultisols Jatinangor. The experiment was conducted from April to November 2017 at Ciparanje Experimental Garden, Faculty of Agriculture, Universitas Padjadjaran, using a simple randomized block design consisting of 10 treatments and replicated 3 times. The organo-mineral ingredients used consist of a combination of Humic Acid (6; 8; 10 kg/ha); Dolomites (100; 150; 200 kg/ha); Natural Phosphates (250; 300; 350 kg/ha); also Zeolites (150; 200; 250 kg/ha). The results showed that ameliorant combination had significant effects on soil pH, P-available, and Mn Total, also the yield of maize. Dosage of 8 kg/ha of Humid Acids + 200 kg/ha of Dolomites + 350 kg/ha of Natural Phosphates + 250 kg/ha Zeolite, has indicated better result based on variable experiment.Keywords: maize, organo-mineral, Humic acid, dolomite, phosphate, ultisols